Changes in body composition and cardiometabolic health after detraining in older men with osteosarcopenia: 6-month follow-up of the randomized controlled franconian osteopenia and sarcopenia trial (frost) study - Kemmler, Wolfgang; Schöne, Daniel; Kohl, Matthias; von Stengel, Simon (Clinical Interventions in Aging, 2021)
Purpose: Temporary cessation of exercise but maintenance of habitual physical activity might be a frequent situation in older people’s lives. Particularly the COVID-19 induced lockdown of exercise training facilities with individual outdoor activities still being allowed might be a blueprint for this potentially harmful scenario. Thus, the aim of the present study was to determine the effects of 6 months of detraining after 18 months of high-intensity resistance exercise (HIT-RT) on body composition and cardiometabolic outcomes in predominately obese older men with osteosarcopenia. Materials and Methods: Community-dwelling predominately obese men 72–91 years old with low muscle and bone mass (n=43) were randomly assigned to an 18-month HIT-RT (EG: n=21) or a non-training control group (CG, n=22). After the intervention, participants of the EG discontinued HIT-RT for 6 months, but increased their habitual physical activity. Study outcomes were group differences in detraining changes (“effects”) for lean body mass (LBM), total and abdominal body fat rate (determined by dual-energy x-ray absorptiometry) and the Metabolic Syndrome Z-Score (MetSZ). We applied an intention-to-treat analysis with multiple imputation to analyze the data. Results: After the 18-month HIT-RT, we observed significant positive training effects for LBM, total and abdominal body fat rate and the MetSZ (all p<0.001). Abrupt cessation of HIT-RT for 6 months resulted in significantly higher unfavorable changes in the HIT-RT compared with the CG for LBM (p=0.001), total body fat (p=0.003) and the MetSZ (p=0.003), apart from abdominal body fat (p=0.059). However, significant overall effects were still present after 24 months for LBM and body fat indices but not for the MetSZ. Conclusion: The present study clearly indicates the unfavorable effects of 6 months of detraining after HIT-RT. Correspondingly, exercise protocols particularly for older people should focus on continuous exercise with short regeneration periods rather than on intermitted protocols with pronounced training breaks.
CRIS-Team Scopus Importer:2021-04-23
Keywords: Body fat; Detraining; Lean body mass; Metabolic syndrome; Older men; Resistance exercise